ONLINE REVIEWS, CELEBRITY ENDORSERS EFFECT PURCHASE DECISION OF GENERATION Z AT SAMSUNG EXPERIENCE STORE PALEMBANG - Yuni Adinda Putri (Universitas Islam Lamongan, 2024)
This research aimed to explore and explain the influence of online review and celebrity endorser on the customers’ loyalty, with purchase decision as the intervening variable. The research method used was explanatory with quantitative approach. The research location was at Samsung Experience Store Palembang, with consumers’ population the people who used samsung brand smartphone. Sample selection was carried out by using purposive sampling method, and 57 respondents were involved in this research. Results showed that there was influence of online review and celebrity endorser on the customers’ loyalty with purchase decision as the intervening variable.